MEANS OF SOCIAL EMOTIONAL PHYSICAL DEVELOPMENT OF CHILDREN AND FORMATION OF A HEALTHY LIFESTYLE (E Global Congress, 2023)
In this article, we will discuss the means of social, emotional, and physical development of children and the formation of a healthy lifestyle. We will explore the strategies that can be helpful in promoting healthy development in children, including healthy eating habits, physical exercise, social interaction, and emotional regulation.